Beyond Trends: A Bibliometric Analysis Unveiling the Educational, Psychological, Contextual, and Systemic Dimensions of Sustainability in Higher Education - Luzolo, Inês; Jorge, Elói; Almeida, Luis (European Journal of Sustainable Development, 2025)
This study presents a bibliometric analysis of literature focusing on sustainability in higher education, based on a review of 270 publications indexed in the Web of Science from 2014 to 2024. By employing RStudio and Bibliometrix for the analysis, trends, gaps, and contributions were identified, emphasising the most relevant scientific journals, author productivity over time, institutional and international collaborations, and the most prevalent keywords within the context of sustainable institutions. The study’s findings revealed four thematic areas across two axes: one focusing on the educational and psychological dimensions of sustainability and the other on the contextual and systemic factors shaping education for sustainability. This study has contributed to a deeper understanding of the integration of sustainability in higher education. This objective was achieved by presenting a full overview of current trends, existing gaps, and potential future research areas Keywords: education, higher education institutions, sustainable development, sustainability, systemic factors